The Role of Nested Systems in EFL Students' Willingness to Communicate (WTC) and Engagement - Gu, Lingang; Sun, Pingping (Frontiers in Psychology, 2021)
Language learning is a complex process with many intra-personal and inter-personal processes which are nested within smaller systems, themselves. Willingness to Communicate (WTC) and student’s engagement are two of many complicated, multi-faceted, and dynamic variables in L2 learning which have mostly been explored via quantitative, correlational, and one-shot methodologies. However, such a research trend only provided a snapshot of SLA variables’ nature and dynamism. Against this shortcoming, the current study aims to present the conceptualizations, applications, and implications of complexity dynamic system theory (CDST) for investigating L2 earner-psychology variables, especially WTC and engagement. In so doing, the definitions, dimensions, and key properties of the two constructs were explained. In the end, a series of research gaps, implications, and future directions are suggested for future researchers in this territory.